PERGULATAN PEMIKIRAN ISLAM DI ACEH - Syafieh, Syafieh (At-Tafkir, 2016)
Typology thinking of Islamic society organizations in Aceh thereare three types including the first typology of traditional Islamicthought. Community organizations are included in the thinking oftraditional Islam in Aceh is 1) HUDA (Associationof AcehneseDayah Ulama), 2) MUNA (Majelis Ulama Nanggroe AcehDarussalam), 3) NU (Nahdlatul Ulama), and 4) Al-Wasliyah,second, typologies of thought Modern Islam represented byMuhammadiyah, and the third, the typology of fundamentalistIslamic thought. Fundamentalist Islamic Thought in Aceh isrepresented by 1) Hizb ut-Tahrir Indonesia (HTI) 2) The IslamicDefenders Front (FPI). However provide a typology oftraditional Islam, modern Islam, and Islamic fundamentalistIslam to the community organizations in Aceh is irrelevantbecause the organasasi movement today is beyond thedichotomous typology.